Underwater noise impact of a ferry route on dive patterns of transiting Baltic ringed seals - Muhammad Saladin Prawirasasra; Mart Jüssi; Mirko Mustonen; Aleksander Klauson (Estonian Journal of Earth Sciences, 2022)
To understand the impact of underwater anthropogenic noise on marine life, it is crucial to collect more data about the onset of behavioural reactions of marine species. Three free-ranging ringed seals (Phoca hispida botnica) were marked with GPS tags to track their movements in the Baltic Sea. The tracking data showed that ringed seals regularly transit between their haul-outs in the VÃ¤inameri and foraging areas in the southern part of the Gulf of Riga. On their way, the ringed seals pass through the Suur vÃ¤in (Suur Strait) and have to cross the VirtsuâKuivastu ferry route, where they are likely exposed to underwater ship-borne noise. Ringed sealsâ dive profiles were studied for the presence of avoidance reactions in response to ship-radiated noise. As a result, some dive profile irregularities were noticed in the form of deep dives or multiple surfacings. The received level (RL) causing the disturbance in ringed sealsâ behaviour was estimated based on sound propagation modelling. The obtained results are generally in line with previously reported studies on captive harbour seals and free-ranging grey seals. However, behavioural reactions observed in the current study are unlikely to adversely affect the energy budgets of ringed seals due to the short exposure time.